A Collecting Collision Tree Protocol for RFID Tag Identification with Capture Effect. (10th September 2015) - Qing, Yang; Jiancheng, Li; Hongyi, Wang
Multitag identification is one of the main advantages of the radio frequency identification (RFID) system. In the RFID system, the capture effect often happens in the real environment. When the capture effect occurs, the reader will not completely identify the tags in its scope. In many RFID applications, to get the real-time number of tags, the reader identifies the tags repeatedly. In these cases, the tag in the reader's scope is a staying tag or an arriving tag. The reader already stores the IDs of all staying tags, so it can just verify the existence of these tags to rapidly identify them. As a result, the reader can spend the main time in recognizing arriving tags. To cope with the capture effect and identify staying tags rapidly, this paper presents a collecting collision tree protocol for RFID tag identification with capture effect (CCT). In CCT, a collecting mechanism is adopted and a lot of staying tags can be recognized in a slot. What is more, the reader can identify all tags in its range when the capture effect happens. Finally, various analysis and simulation results show that CCT outperforms the existing algorithms significantly.